مراسلات الإمام النورسي للشخصيات - جمعًا ودراسة - قريشي, لبنة; غرايسة, زبيدة; جديدي, وجدان (جامعة الوادي university of eloued, 2019)
تناكلت ىذه الدراسة مراسلات الإما النورسي للشخصيات بصعا كدراسة، حيث تناكلنا، فيها ثلاثة مباحث، فابؼبحث الأكؿ يندرج برت عنواف التعريف بالشخصية، كابؼبحث الثاني تناكؿ التعريف بابؼراسلات مفهوما عاما كأبنية ابؼراسلات في الدعوة إلى ا﵁، كابؼبحث الثالث الشخصيات التي راسلها. ˗ بديع الزماف النورسي ىو أحد دعاة الإسلا، ستَتو مليئة بابؼواقف الصعبة، قا النورسي بجهود عديدة، فألف العديد من ابؼراسلات في تاريخ الدعوات الإسلامية ابؼعاصرة كالتي ˗ ربضو ا﵁ كاف ىدفها إنقاذ الإبياف كعودة الإسلا إلى ابغياة كعودة ابؼلليتُ إلى دينه كقرنه ، كبركي شرع ا﵁ في سائر أمورى كأحوابؽ . كظهرت عليو علامات النبوغ كالفطنة منذ صغره فتتليذ على العديد من ابؼشايخ منه سيد نور بؿيد كابؼلأ بؿيد الأفندم، حيث خلف الشيخ العديد من الكتب أبنها: رسائل النور. توفي ربضة ا﵁ عليو في 25 رمضاف 1374 ق ابؼوافق ؿ 23 مارس This study conducts the analyses of the correspondences of Imam Nursí to the figures in which we devide the work into three sections. The first one is about the biography of Imam Nursi, the second section is mainly on the general definition of the correspondences and its significance in calling to Allah, and the third one is about the figures whom he has been contacting The wonder of the age Nursi is one of the advocates for Islam religion, his life is full of difficulties . Nursi (may Allah have mercy on him) gave a great amount of effort, he wrote several correspondences in the history of Modern Islamic Dawah which aim to save the belief and bring Islam back to our lives and Muslims to Qur'an and religion,and to work with sharia in all their aspects of life. In very young age, the signs of brilliance have emerged in him, he has been taught by several scholars including Sayed noor Mohammed and Mohammed alafandi , and he wrote many books such as: The Risale-i Nur Collection He passed away on 25th of Ramadan 1374(March23rd,1960 )
دعوة